2021
DOI: 10.1101/2021.09.22.461286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inducible CRISPR activation screen for interferon-stimulated genes identifies OAS1 as a SARS-CoV-2 restriction factor

Abstract: Interferons establish an antiviral state in responding cells through the induction of hundreds of interferon-stimulated genes (ISGs). ISGs antagonize viral pathogens directly through diverse mechanisms acting at different stages of viral life cycles, and indirectly by modulating cell cycle and promoting programmed cell death. The mechanisms of action and viral specificities for most ISGs remain incompletely understood. To enable the high throughput interrogation of ISG antiviral functions in pooled genetic scr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…In following studies, LY6E was found to enhance post-attachment viral entry of flaviviruses and influenza A virus (Mar et al 2018; Hackett and Cherry 2018) as well as HIV-1 (Yu, Liang, and Liu 2017). In more recent screening efforts, LY6E was identified as a restriction factor for coronaviruses (Pfaender et al 2020; Wickenhagen et al 2021; Danziger et al 2022; Mac Kain et al 2022) including members of the betacoronavirus genus: mouse hepatitis virus (MHV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, our understanding of how LY6E controls coronavirus pathogenesis in vivo has only been demonstrated with MHV (Pfaender et al 2020), due to previous limitations of available mouse models for studying SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…In following studies, LY6E was found to enhance post-attachment viral entry of flaviviruses and influenza A virus (Mar et al 2018; Hackett and Cherry 2018) as well as HIV-1 (Yu, Liang, and Liu 2017). In more recent screening efforts, LY6E was identified as a restriction factor for coronaviruses (Pfaender et al 2020; Wickenhagen et al 2021; Danziger et al 2022; Mac Kain et al 2022) including members of the betacoronavirus genus: mouse hepatitis virus (MHV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, our understanding of how LY6E controls coronavirus pathogenesis in vivo has only been demonstrated with MHV (Pfaender et al 2020), due to previous limitations of available mouse models for studying SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…The main protease of coronaviruses, commonly associated with viral polyprotein precursors processing, is essential to antagonize intracellular antiviral defenses ( 37 ). To examine how the presence of M pro affects the expression of IFN-dependent genes, we performed quantitative real-time RT-PCR for four well-characterized ISGs that inhibit SARS-CoV-2 infection, namely ISG15, ISG56, IFIT3, and OAS1, following overexpression of M pro in human embryonic kidney cells (HEK-293T) ( 28 , 38 , 39 ).The cells were first treated for eight hours with 0, 250, 500, 1000, or 2000 U/mL of recombinant human IFN-α, and then collected for measuring mRNA levels of IFIT3 using quantitative PCR. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ISGs like the IFIT family, including IFIT1 (ISG15), IFIT2 (ISG54), IFIT3, and IFIT5 in humans, bind the translation initiation factor complex to suppress viral protein production ( 25 , 26 ). Moreover, ISGs such as OAS proteins are enzymes that activate cellular ribonuclease L (RNase L), which efficiently degrades viral genomes ( 27 , 28 ). However, the signaling leading to the expression of ISGs is globally impaired when histone deacetylases (HDACs) activity is restrained by HDACs inhibitor trichostatin A (TSA).…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect may result from the alternative splicing in 2'-5'-Oligoadenylate Synthetase (OAS1) observed in our study in the infected patients. The OAS1 was previously described as a SARS-CoV-2 strong restriction factor capable of inhibiting viral infection [114]. OAS1 isoforms have been shown to differ in their antiviral activities [115].…”
Section: Discussionmentioning
confidence: 99%